Museum of Nias Earthquake (Vernacular Architecture) - Oscar A. Halawa; Nelson Siahaan (International Journal of Architecture and Urbanism, 2019)
Museum of Nias Earthquake is about a place to reintroduce local wisdom from Nias Island that related to their history and traditional building technology in response to earthquake disasters, with the aim of education and tourism. Nowadays, modern civilization marginalized a local culture. Vernacular themes are a solution in presenting the results of local-themed design. It will become an example of how to apply the local wisdom in contemporary building design, with the aim of reintroducing local sense. To achieve a vernacular theme, it started by using local materials, abstraction of local traditional houses, application of symbols and meanings from traditional building cosmology, and using observation and literature methodology. The result of this design is to meet the community needs for tourism objects that have a locality feel in Gunungsitoli City, Nias.